Impact of Preoperative Cardiology Consultation on Perioperative Complications in Elective Non-Cardiac Major Surgery: A Comparative Study at a Tertiary Care Hospital - Sharif , Salman; Adeel Ur Rehman; Naeem , Kashif; Masood , Naveed; Izhar , Hafiz Muhammad Furqan; Nasiuddin , Asir (Indus Journal of Bioscience Research, 2025)
Background: Perioperative complications pose significant risks for patients undergoing elective major non-cardiac surgery, particularly those with pre-existing cardiovascular risk factors. These problems may lead to increased morbidity, extended hospitalizations, and greater healthcare expenditures. Consequently, identifying techniques to mitigate perioperative hazards has emerged as a priority in clinical settings. Objective: To compare the frequency of perioperative complications in patients who received and did not receive cardiology consultation prior to undergoing non-cardiac elective surgery at a tertiary care hospital. Method: A Descriptive Study was conducted at the Department of Anesthesiology, The Indus Hospital, Karachi, Pakistan, for six months after the approval of the synopsis from March 26, 2021, to September 26, 2021. All patients meeting the inclusion criteria were included. Informed consent was obtained after explaining the procedure, risks, and benefits. A brief history for demographic data like age and gender was recorded, and perioperative complications were assessed on the third postoperative day. Data were electronically stored for research purposes. Results: The age of patients ranged from 36 to 70 years, with a median of 57 and an interquartile range of 14 (C.I 53.94–56.93). Among them, 91 (61.1%) were male, and 58 (38.9%) were female. Acute coronary syndrome was found in 8 (5.4%), arrhythmia in 9 (6.0%), while no patients had acute heart failure. No significant difference was observed between those who received cardiology consultation and those who did not (P-Value: 0.133 & 0.086). Conclusion: No significant difference was noted among patients who received and did not receive cardiology consultation before non-cardiac elective surgery.